(De-)Politicization Trajectories in an Anti-Austerity Contentious Cycle. Social Clinics-Pharmacies Solidarity structures in Greece - Kotronaki, Loukia; Christou, Stella (PARTECIPAZIONE E CONFLITTO, 2019)
This article aspires to contribute to the ongoing literature on collective action in times of crisis. Our emphasis is on what has been considered the anti-austerity protest cycle’s most novel pattern of everyday resistance, i.e., the “solidarity” frame and its concomitant forms of direct social action. For that purpose, we focus on the most emblematic case of solidarity politics in Greece, the Clinics-Pharmacies Solidarity Structures (SCPSs). Emerging in 2011, SCPSs spread throughout the country only to decline after the introduction of Health Reform by the left-wing government of SYRIZA. By adopting a relational approach highlighting the interplay between waves of contention, the fluctuating institutional environment, and broader social and structural processes in the background of a hollowed welfare state, we demon-strate the politicization potential of solidarity direct social action, as well as its antipodal dynamic: depoliticization and movement dissolution. We argue that the latter was the result of a double process: (a) the selective co-optation of soli-darity structures by an institutional actor (SYRIZA), setting in motion movement-internal polarization, and (b) the discur-sive subordination of solidarity frames and activities to the “realm of necessity” as prescribed by the rationality of con-tinuing austerity politics.